2021
DOI: 10.1101/2021.08.19.21262139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predominance of antibody-resistant SARS-CoV-2 variants in vaccine breakthrough cases from the San Francisco Bay Area, California

Abstract: Associations between vaccine breakthrough cases and infection by SARS coronavirus 2 (SARS-CoV-2) variants have remained largely unexplored. Here we analyzed SARS-CoV-2 whole-genome sequences and viral loads from 1,373 persons with COVID-19 from the San Francisco Bay Area from February 1 to June 30, 2021, of which 125 (9.1%) were vaccine breakthrough infections. Fully vaccinated were more likely than unvaccinated persons to be infected by variants carrying mutations associated with decreased antibody neutraliza… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…These cases of reinfection as well as those previously reported for the variants P.2/Gamma in Brazil 17,23,24 are consistent with the described capability of viruses carrying the substitution S:E484K to escape from anti-SARS-CoV-2 antibodies 7-9 and to cause SARS-CoV-2 breakthrough infections in vaccinated persons 37-39 . These observations are also consistent with previous studies that showed that variant Gamma is more resistant to neutralization by sera from convalescent/vaccinated patients than ancestral Wuhan related strains 40-45 .…”
Section: Discussionsupporting
confidence: 90%
“…These cases of reinfection as well as those previously reported for the variants P.2/Gamma in Brazil 17,23,24 are consistent with the described capability of viruses carrying the substitution S:E484K to escape from anti-SARS-CoV-2 antibodies 7-9 and to cause SARS-CoV-2 breakthrough infections in vaccinated persons 37-39 . These observations are also consistent with previous studies that showed that variant Gamma is more resistant to neutralization by sera from convalescent/vaccinated patients than ancestral Wuhan related strains 40-45 .…”
Section: Discussionsupporting
confidence: 90%
“…Such discussion is all the more needed that vaccine efficiency has been reported dropping far from 100% with time and variants for most vaccines, including Pfizer, and that their ability to stop transmission by asymptomatic infection is questionable (Hacisuleyman et al, 2021;Servellita et al, 2021). It is most probable that vaccination alone will not be enough to stop the epidemic spreading via airborne contamination, because present vaccines do not provide a 100% immunity, especially with new variants such as omicron, although it will result in a strong reduction of the gravity of infection and of its consequences.…”
Section: Implications Of Increased Airborne Contamination For Health ...mentioning
confidence: 99%
“…We analyzed a large sample that represents the general population of the U.S. west coast. Previous published studies in the U.S. (9,(23)(24)(25)(26)(27) are limited to a cohort with specific characteristics, such as health-care workers (6,15,23,27), patients with specific comorbidities (28)(29)(30), veterans (9,24,29,31), patients of academic hospitals (32,33). PSJH is a community-served hospital that covers five states of the west coast in both rural and urban areas.…”
Section: Strengths and Limitationsmentioning
confidence: 99%